The Northernmost Volcanoes in South America (Colombia, 5–6°N): The Potentially Active Samaná Monogenetic Volcanic Field - Sánchez-Torres, Laura; Murcia, Hugo; Schonwalder-Ángel, Dayana (Frontiers in Earth Science, 2022)
The northernmost volcanism in South America (5–6°N) is defined by the presence of several monogenetic volcanic edifices in Colombia, which have been grouped within the Samaná monogenetic volcanic field. Few volcanoes have been studied so far, but they are recognized as a cluster of volcanoes of intermediate-to-acid composition, formed by both explosive and effusive eruptions. This study aims to 1) characterize four more monogenetic volcanic edifices as part of the Samaná field, 2) highlight the potentially active volcanism in an area previously defined as non-volcanogenic, and 3) give insights into the magmatic evolution of the scarcely studied evolved monogenetic volcanism linked to subduction zones worldwide. To achieve these aims, this study uses petrography, mineral chemistry, whole-rock geochemistry, geochronological analyses, and geothermobarometric calculations. The analyses indicate that the field is formed by at least seven volcanoes with similar composition and that it is long-lived and potentially active. Mineralogically, the erupted products host plagioclase (An26–74) and amphibole (magnesio-hastingsite, tschermakite, and occasionally mangesio-hornblende) as the most abundant phases, although orthopyroxene (enstatite; Wo2–3, En70–76, Fs21–28) and clinopyroxene (diopside and augite; Wo44–45, En41–42, Fs13–15, and Wo42–44, En46–47, Fs10–11) also appear. Less abundant phases such as olivine (Fo81–88), biotite (magnesiobiotite), quartz, and Fe–Ti oxides (Usp4–89 Mag96–11, and Ilm61–92 Hem39–8) were also recognized. Chemically, the volcanoes are of andesitic-to-dacitic composition with calc-alkaline affinity and show similar behavior of LILE, HFSE, and REE, which is typical for magmatism in subduction environments. Ages yield a range between 1.32 ± 0.06 Ma (K/Ar) and 16,919 ± 220 years (14C). The results also indicate that the volcanoes share a common magmatic source that fed the individual eruptions and that the magma differentiation is mainly controlled by processes of fractional crystallization, although evidence of magma recharge processes or magma mixing and assimilation as a minor process are also recognized. Geothermobarometric calculations suggest that the different mineral phases are crystallized between 1,194 and 687 °C and a pressure between 0.88 and 0.19 GPa. This indicates that the aforementioned processes occurred not only at the main magmatic reservoir (∼33–21 km depth) but also at different stagnation zones at shallower levels of the crust (∼7–5 km). Taking this into account, it is shown that the magma evolution of this monogenetic field is more complex than individual batches of magma reaching the surface uninterrupted, as is normally described for monogenetic volcanic fields of more mafic compositions in other tectonic settings.